PENGARUH GAYA KEPEMIMPINAN KEPALA SEKOLAH DAN MANAJEMEN PENDIDIKAN TERHADAP SEMANGAT KERJA GURU DI SMA NEGERI SE KABUPATEN ASAHAN - Mayrio Arizona Silaen (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: The low work spirit of teachers and weak work ethic, which can be seen from the behavior of teachers who tend to be less active and easily carried away by emotions, have an impact on the quality of learning and student achievement. The survey results also show that the quality of learning has decreased, which is indicated by low literacy and numeracy scores. The formulation of the research problem is 1) How much influence does the principal's leadership style have on the work spirit of teachers in State Senior High Schools in Asahan Regency, 2) How much influence does educational management have on the work spirit of teachers in State Senior High Schools in Asahan Regency, 3) How much influence does the principal's leadership style and educational management simultaneously have on the work spirit of teachers in State Senior High Schools in Asahan Regency. The population of this study were 562 state senior high school teachers in Asahan Regency. Because the number of teachers as a population is more than 100, a sample of 15% was taken so that the sample totaled 84 teachers. The data analysis technique used was correlation analysis using the SPSS version 22 program. The tests used were the t-test, F-test and coefficient of determination.  The results of the study showed that partially the principal's leadership style had an effect on the work spirit of teachers in State Senior High Schools in Asahan Regency. There is an influence of 70.90% where the better the principal's leadership style, the higher the teacher's work enthusiasm will be. Partially, educational management influences the work enthusiasm of teachers at State Senior High Schools in Asahan Regency. There is an influence of 57.40% where the better the educational management, the higher the teacher's work enthusiasm will be. The principal's leadership style and educational management have an influence of 93.70% on the work enthusiasm of teachers at State Senior High Schools in Asahan Regency. The determination coefficient of 87.50% of the variation in teacher job satisfaction can be explained by the principal's leadership style and educational management simultaneously, while the remaining 12.50% is explained by other factors not examined in this study such as organizational culture factors and work discipline factors. Keywords: Leadership Style, Educational Management, Teacher Work Spirit Abstrak: Rendahnya semangat kerja guru dan lemahnya etos kerja, yang terlihat dari perilaku guru yang cenderung kurang aktif dan mudah terbawa emosi, berdampak pada kualitas pembelajaran dan prestasi siswa. Hasil survei juga menunjukkan bahwa kualitas pembelajaran mengalami penurunan yang ditandai dengan rendahnya skor literasi dan numerasi. Rumusan masalah penelitian ini adalah 1) Seberapa besar pengaruh gaya kepemimpinan kepala sekolah terhadap semangat kerja guru di SMA Negeri Se Kabupaten Asahan, 2) Seberapa besar pengaruh manajemen pendidikan terhadap semangat kerja guru di SMA Negeri Se Kabupaten Asahan, 3) Seberapa besar pengaruh gaya kepemimpinan kepala sekolah dan manajemen pendidikan secara simultan terhadap semangat kerja guru di SMA Negeri Se Kabupaten Asahan. Populasi penelitian ini guru sma Negeri Se Kabupaten Asahan sebanyak 562 orang guru. Karena jumlah guru sebagai populasi lebih dari 100 maka diambil sampel 15 % sehingga sampel berjumlah 84 guru. Teknik analisis data yang digunakan adalah analisis korelasi dengan menggunakan program SPSS versi 22. Uji yang digunakan adalah uji t, uji F dan koefisien determinasi. Hasil penelitian menunjukkan bahwa secara parsial gaya kepemimpinan kepala sekolah berpengaruh terhadap semangat kerja guru pada SMA Negeri Se Kabupaten Asahan.  Terdapat pengaruh sebesar 70,90 % dimana semakin baik gaya kepemimpinan kepala sekolah maka semangat kerja guru juga akan semakin tinggi. Secara parsial manajemen pendidikan berpengaruh terhadap semangat kerja guru pada SMA Negeri Se Kabupaten Asahan.  Terdapat pengaruh sebesar 57,40 % dimana semakin baik manajemen pendidikan maka semangat kerja guru juga akan semakin tinggi. Gaya kepemimpinan kepala sekolah dan manajemen pendidikan mampunyai pengaruh sebesar 93,70 % terhadap semangat kerja guru SMA Negeri Se Kabupaten Asahan.  Koefisien determinasi sebesar 87,50 % variasi kepuasan kerja guru dapat dijelaskan oleh gaya kepemimpinan kepala sekolah dan manajemen pendidikan secara serempak, sedangkan sisanya 12,50 % lagi dijelaskan oleh faktor lain yang tidak diteliti dalam penelitian ini seperti faktor budaya organisasi dan faktor disiplin kerja. Kata kunci: Gaya Kepemimpinan, Manajemen Pendidikan, Semangat Kerja Guru